2021
DOI: 10.3390/land10040355
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Agricultural Land Reclamation on Soil Nutrient Contents, Pools, Stoichiometry, and Their Relationship to Oat Growth on the East China Coast

Abstract: Agricultural land reclamation of coastal tidal land (CTL) with organic amendments may modulate the soil properties, and therefore promote crop growth. However, the linkages between soil nutrient contents, pools, stoichiometry, and crop growth under the supplement of organic amendments in CTL is limited. In this study, six treatments including the control (CK), organic manure (OM), polyacrylamide plus organic manure (PAM + OM), straw mulching plus organic manure (SM + OM), buried straw plus organic manure (BS +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The measured landscape metrics were analyzed by one-way ANOVA to test the significant differences between the constructed wetlands and natural wetlands [28]. Meanwhile, the Pearson correlation analysis was employed to explore the significant relationship between economic indicators and landscape metrics [29].…”
Section: Discussionmentioning
confidence: 99%
“…The measured landscape metrics were analyzed by one-way ANOVA to test the significant differences between the constructed wetlands and natural wetlands [28]. Meanwhile, the Pearson correlation analysis was employed to explore the significant relationship between economic indicators and landscape metrics [29].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the treatment COF at 1.80 kg/m 2 was also well separated from CCF, indicating that the bacterial community structure of The average fungal OTUs number of COF at 0.45, 0.90, 1. 35 1b). In general, the average fungal OTUs number was significantly increased (9.8% to 20.3%) by COF at 0.45 and 1.35 kg/m 2 , SM at 0.45, 0.75 and 1.05 kg/m 2 and chemical fertilizer, was significantly reduced (9.4% to 15.6%) by MR at 3.00 and 3.75 kg/m 2 , and was unaffected by all of the other biological fertilizer treatments compared to the control (Figure 1d).…”
Section: Effects Of Different Organic/chemical Amendments In Soil Mic...mentioning
confidence: 98%
“…Furthermore, other studies have also shown that the soil OMC and the quality of newly reclaimed land could be effectively improved by increasing the use of organic fertilizers. The measures include planting winter legume crops, returning crop stems and stalks to the field, promoting the use of commercial organic fertilizer, comprehensively utilizing agricultural and animal husbandry wastes, and making compost by using rural litter, other plant residues, and gully soil [31][32][33][34][35][36][37][38].…”
Section: Effects Of Different Organic/chemical Amendments On Soil Ph ...mentioning
confidence: 99%
“…In agreement with the results of this study, a similar observation of an increase in OMC was observed by Renet al [ 17 ] and Li et al [ 4 , 27 ]. Furthermore, other studies have also shown that the soil OMC could be effectively improved by planting winter legume crops, returning crop stems and stalks to the field, comprehensively utilizing agricultural and animal husbandry wastes, and making compost by using rural litter and gully soil [ 28 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Therefore, it can be inferred that commercial organic fertilizers have great potential to improve soil quality of the new reclamation soil.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies have revealed that the fungi from the genus Gibberella have been reported to be the pathogen of many leaf- and soil-borne diseases [ 53 ]. However, Mortierella in the rhizophere of wheat is significantly associated with increasing crop growth and yield, and the increase in relative abundance of Mortierella may promote plant growth [ 34 ]. The conflict effect on the relative abundance of Mortierella and Gibberella revealed the complexity of the soil fungal community.…”
Section: Resultsmentioning
confidence: 99%